Carbohydrate Determinants in Ferret Conjunctiva are Affected by Infection with Influenza H1N1 Virus. (21st June 2013) - Kirkeby, Svend; Martel, Cyril J. M.; Aasted, Bent; Vorum, Henrik
Abstract: Background : Carbohydrates often accomplish as cell-surface receptors for microorganisms and influenza virus preferentially binds to sialic acid through the viral haemagglutinin. The virus may attach not only to the epithelium in the airways, but also to the surface ocular epithelium. Purpose : To decide if ferrets can be used to study virus induced conjunctivitis and to evaluate changes in the conjunctival glycosylation pattern during an influenza attack. Methods : Ferrets were infected with H1N1 influenza virus via nasal inoculation. The in situ carbohydrate expressions in eyelid sections from ferrets 0 to 10 days after infection was examined using lectin- and immunohistochemistry. Results : The conjunctival cells became hypertrophic with appearance of both PAS positive and PAS + Alcian Blue stained cells 5–6 days after inoculation. The binding of three sialic acid detecting lectins were investigated: WGA, MAA2 and SNA1. While none of them stained conjunctival epithelial cells in the non-infected ferrets to any extent, there was a positive conjunctival reaction in the infected ferret after incubation with all three lectins. Binding of a MUC1 antibody that seems to detect sialylated determinants in the mucin molecule indicates that MUC1 is de novo expressed in most of the squamous conjunctival cells at the start of the influenza infection. MUC5AC positive epithelial cells, probably goblet cells, proliferate in the diseased conjunctiva. Conclusion : Nasal inoculation of H1N1 virus to ferrets has an effect on the conjunctival cells and change their expression of glycans. Synthesized glycans are an integral part of the tear film and the present study contributes to reveal the changes that occur in the surface epithelium in the eyelid and thereby to elucidate the pathophysiology of the virus mediated conjunctivitis. Ferrets are suitable animal models to study human conjunctivitis mediated by human influenza virus.